Prospective Evaluation of Changes in Pain Levels, Quality of Life and Functionality After Low Dose Radiotherapy for Epicondylitis, Plantar Fasciitis, and Finger Osteoarthritis - Rogers, Susanne; Eberle, Brigitte; Vogt, Deborah R.; Meier, Elisabeth; Moser, Lorenz; Gomez Ordoñez, Silvia; Desborough, Susanne; Riesterer, Oliver; Takacs, Istvan; Hasler, Paul; Bodis, Stephan (Frontiers in Medicine, 2020)
Background: The objective benefits of low dose radiotherapy (LDRT) for non-malignant joint disorders are controversial. This study evaluated changes in pain, quality of life (QoL) and function after LDRT for epicondylitis, plantar fasciitis and finger osteoarthritis. Materials and Methods: Patients over 40 years old with epicondylitis, plantar fasciitis and finger osteoarthritis were had pain following at least 6 months of conservative therapy. Patients received 0.5 Gy LDRT twice weekly for 4 weeks repeated once after 8 weeks in patients who failed to achieve complete pain relief. Patients assessed their pain according to the visual analog scale. Handgrip strength was measured with an isometric dynamometer and the fast self-paced walking test was used in patients with plantar fasciitis. QoL was evaluated according to the EQ-5D and HAQ-DI questionnaires. Results: Outcomes for 157 patients (204 sites) were documented at 2, 6 and 12 months after last LDRT. Pain reduction at rest (p<0.001), during activity (p<0.001) and increase in handgrip strength (extension p<0.001, flexion p=0.002) were highly significant for patients with lateral epicondylitis. Patients with medial epicondylitis reported pain relief at rest (p=0.041) and during activity (p=0.041) and significant increase in handgrip strength (p=0.022). Patients with plantar fasciitis reported pain reduction at rest (p<0.001), during activity (p<0.001) and faster walking times (p<0.001). A trend towards improved QoL was observed. Patients with finger osteoarthritis reported significant pain relief during activity (p<0.001) and a gain in handgrip strength (p=0.004), with a trend to both pain relief at rest (p=0.056) and stronger pinch grip (p=0.099). Conclusions: LDRT achieved significant pain relief at rest and during activity and a corresponding objective improvement in handgrip strength in patients with epicondylitis. Pain relief at rest, during activity and improvement in walking time were demonstrated in patients with plantar fasciitis. LDRT achieved pain relief during activity, and handgrip strength was improved in patients with finger osteoarthritis. No significant effect was seen on quality of life measures for these conditions. The observed benefits were maintained 12 months after LDRT for all 3 indications and we recommend this low cost, safe intervention for patients over 40 who have failed prior conservative therapy.